2017
DOI: 10.1155/2017/5047403
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oropharyngeal Microbiota from Children with Asthma and Cystic Fibrosis

Abstract: A genuine microbiota resides in the lungs which emanates from the colonization by the oropharyngeal microbiota. Changes in the oropharyngeal microbiota might be the source of dysbiosis observed in the lower airways in patients suffering from asthma or cystic fibrosis (CF). To examine this hypothesis, we compared the throat microbiota from healthy children (n = 62) and that from children with asthma (n = 27) and CF (n = 57) aged 6 to 12 years using 16S rRNA amplicon sequencing. Our results show high levels of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 42 publications
1
16
0
1
Order By: Relevance
“…This conclusion was supported by the fact that in parallel with LUM/IVA therapy and the described improvements in ventilation homogeneity, there was a marked decrease in total IgG during the first two years of LUM/IVA therapy in the patients with CF. Although only a minority of patients with CF showed elevated IgG at baseline, an increased immunological activity due to chronic inflammation can be assumed as part of the pulmonary CF disease in all patients with CF [ 46 , 47 ]. If a significant IgG decrease is now observed, it can be assumed that the reduced inflammatory activity in these patients with CF is associated with the partial correction of the CFTR defect under LUM/IVA therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion was supported by the fact that in parallel with LUM/IVA therapy and the described improvements in ventilation homogeneity, there was a marked decrease in total IgG during the first two years of LUM/IVA therapy in the patients with CF. Although only a minority of patients with CF showed elevated IgG at baseline, an increased immunological activity due to chronic inflammation can be assumed as part of the pulmonary CF disease in all patients with CF [ 46 , 47 ]. If a significant IgG decrease is now observed, it can be assumed that the reduced inflammatory activity in these patients with CF is associated with the partial correction of the CFTR defect under LUM/IVA therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, our cohort of CF adults had more advanced lung disease and a microbial community which was much less diverse (median SDI 1.21 (IQR 0.5–1.8) – and thus less likely to experience significant perturbations [ 37 , 38 ]. It is possible a younger cohort of individuals with CF with more diverse microbial communities – more in keeping with those of asthma, COPD, and nCFB [ 39 , 40 ] – may be more likely to demonstrate a change. However, other studies focusing on classical CF methods have also found that azithromycin treatment had no major impact on microbiological outcomes in a CF pediatric cohort with early P. aeruginosa infection [ 11 ] or in sputum bioburden [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that microbiota in patients with asthma differs from that in healthy subjects (with an increase in Moraxella sp., and a decrease in Prevotella spp.) [5,12], or those with cystic fibrosis [13].…”
Section: Introductionmentioning
confidence: 99%